Teaching Note—Popular Science Writing in a Social Work Program: From an Idea to a Student Anthology. - Larsson, Per Olof; Högberg, Håkan; Lundälv, Jörgen (Journal of Social Work Education)
The purpose of this article is to describe how students, as part of their education, published course papers in an anthology. Over a period of 2.5 years, we followed students in an undergraduate social work program. The course, which focused on long-term illnesses and the functional barriers people with disabilities face in society, ended with a graded seminar in which students presented written manuscripts based on the course content. The papers were later compiled into a student anthology. The publishing process involved several participants, including teachers, a book publisher, and a disability organization. This article describes experiences based on the perspectives of the students, the disability organization, the publisher, and the editor. It ends with advice and recommendations for those who want to use this method.